Income inequality developments in the Great Recession - Hellebrandt, Tomas (Luxembourg, 2014)
"The Great Recession has increased concerns over the fairness of the distribution of wealth and income in many societies. Using data on eight advanced economies (Germany, Greece, Ireland, Italy, Slovakia, Spain, the United Kingdom, and United States) between 2007 and 2010, I show how the Great Recession affected income inequality in different countries and how families and the state tried to mitigate its impact— through redistributing income within households and through the tax and benefit system. In most countries redistribution within household, through the social safety net and through direct taxes has been largely successful in offsetting the effect on income inequality of increased earnings inequality caused by the rise in unemployment in this pre-austerity period. I discuss some policy lessons that emerge from the varying experiences of different countries."